Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This is on the same theme as in this post, where the Fourier transform was derived using simple function.

Let $f:[0,1] \to [0,1]$ be the Cantor function.
Then $f$ is the cumulative distribution of a Cantor distributed random variable $$ X=\sum_{n=1}^\infty 3^{-n} Y_n $$ where the $Y_n$ are i.i.d. and takes values $0$ and $2$ with equal probability.

In this MO post, it is stated that $$ E(e^{itY_n})=e^{it/2}\cos(3^{-n} t). $$

How do we get that? I have $$ E(e^{itY_n})=\frac{e^{it2/3^n}+1}{2}. $$

Also, it is stated in the post that $$ \hat f(t)=\frac{1}{it} -\frac{1}{it}\hat {f'}(t). $$

How do we get this one? I thought $$ \hat f(t)=\frac{1}{it}\hat {f'}(t) $$ only.

share|cite|improve this question
It makes sense to link to closely related questions that you asked before, since it provides more context and may allow people to build on what's already been done. – joriki Oct 25 '12 at 12:00
@joriki I though this was done automatically somehow. Thanks for notifying me that I should do it explicitly. – Nicolas Essis-Breton Oct 25 '12 at 13:04
up vote 3 down vote accepted

We have \begin{align} E[e^{itX}]&=\prod_{n=1}^{+\infty}E[e^{it3^{-n}Y_n}]\\ &=\prod_{n=1}^{+\infty}\frac{e^{it2\cdot 3^{-n}}+1}2\\ &=\prod_{n=1}^{+\infty}e^{it \cdot 3^{-n}}\cos(t3^{—n})\\ &=\prod_{n=1}^{+\infty}e^{it \cdot 3^{-n}}\prod_{n=1}^{+\infty}\cos(t3^{-n})\\ &=\exp\left(it\sum_{n\geq 1}3^{—n}\right)\prod_{n=1}^{+\infty}\cos(t3^{-n})\\ &=\exp(it/2)\prod_{n=1}^{+\infty}\cos(t3^{-n}). \end{align}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.